Refining the Understanding of Large Cutting Tool Technology in the Baise Basin, South China. (3rd April 2021) - Lei, Lei; Lotter, Matt G.; Li, Dawei; Kuman, Kathleen; Li, Hao
ABSTRACT: Ever since the first discovery of handaxes in the 1970s in the Baise (Bose) Basin in South China, this region has been providing important data that have improved our understanding of Large Cutting Tool (LCT) technology in China. However, presently there are still some obvious shortfalls in our understanding of this very significant cultural paleolandscape. For instance, previous studies have only analyzed small or incomplete sub-samples of much larger collections, especially of the LCTs often from surface contexts, and in addition recent studies have also largely focused on the analysis of LCT morphological indices, versus adopting a more holistic approach that considers fundamental technological attributes. As a result, this study aims to provide a more detailed quantitative assessment of an expanded LCT and artifact sample, and furthermore, provide important insight into the spatial and temporal variability of Large Cutting Tool technology from a wider geographical and environmental perspective.